The Gendered Culture of Scientific Competence: A Study of Scientist Characters in Doctor Who 1963-2013. - Orthia, Lindy; Morgain, Rachel (Sex Roles, 2016)
The present study examines the relationship between gender and scientific competence in fictional representations of scientists in the British science fiction television program Doctor Who. Previous studies of fictional scientists have argued that women are often depicted as less scientifically capable than men, but these have largely taken a simple demographic approach or focused exclusively on female scientist characters. By examining both male and female scientists ( n = 222) depicted over the first 50 years of Doctor Who, our study shows that, although male scientists significantly outnumbered female scientists in all but the most recent decade, both genders have consistently been depicted as equally competent in scientific matters. However, an in-depth analysis of several characters depicted as extremely scientifically non-credible found that their behavior, appearance, and relations were universally marked by more subtle violations of gender expectations. Incompetent male scientists were largely depicted as effeminate and lacking in masculinity. In addition, many incompetent male and all incompetent female scientists served regimes that were problematically effeminate, collectivist and pacifist, or male-rejecting and ruled by women. Although Doctor Who avoids overtly treating women and men unequally, strong codes of masculine capability and prowess nevertheless continue to influence representations of scientific competence, pointing to the continued pervasiveness of such associations within wider Western culture. Professionals working to encourage gender-inclusive practices in science should look to subtle discourses about the masculine culture of science in addition to institutional and structural impediments to participation for women and gender minorities.